VALIDATION OF THE MECG-DP-NS-01 MONITOR IN OSCILLOMETRY AND AUSCULTATION MODES IN PREGNANCY, ACCORDING TO ESH IP-2, BHS AND AAMI PROTOCOLS - S. I. Fedorova; N. V. Kulakov; V. P. Pronina; S. R. Mravyan (Alʹmanah Kliničeskoj Mediciny, 2016)
Background: Arterial hypertension in pregnancy is a major cause of maternal death and perinatal mortality. According to the Russian recommendations, only devices that have been evaluated according to international protocols may be used for ambulatory blood pressure monitoring in pregnancy.Aim: Validation of the MECG-DP-NS-01 upper arm blood pressure monitor manufactured by the DMS Advanced Technologies Ltd., in oscillometry and auscultation modes for ambulatory blood pressure monitoring in pregnancy, according to the ESH International Protocol revision 2010 (ESH-IP2), the BHS protocol revision 1993 and the AAMI standard.Materials and methods: A group of 39 pregnant women at various gestation time (from 9 to 40 weeks, 29.2 ± 9.9 weeks) aged 25 to 43 years (31.9 ± 4.3 years) was recruited for the validation study. Expert and device blood pressure measurements were taken for each patient according to the international protocols.Results: The MECG-DP-NS-01 upper arm blood pressure monitor produced by the DMS Advanced Technologies Ltd. for ambulatory blood pressure monitoring was validated in oscillometry and auscultation modes in pregnancy, according to the BHS protocol revision 1993, the ESH-IP2 and the AAMI standard. The device met an A/A grading for the BHS protocol revision 1993 both in the oscillometry and auscultation modes. The device maintained its A/A grading throughout the low-pressure, medium-pressure and high-pressure ranges.Conclusion: The MECG-DP-NS-01 met all the requirements and, fulfilling the standards of the protocols, is recommended for ambulatory blood pressure monitoring in pregnancy according to BHS protocol revision 1993, ESH-IP2 and AAMI standard. According to the Declaration of Blood Pressure Measuring Device Equivalence signed by the manufacturer, there are no differences that will affect blood pressure measuring accuracy between the MDP-NS-02s “Voshod” upper arm blood pressure monitor produced by the DMS Advanced Technologies Ltd. and the MECG-DP-NS-01, which passed the ESH-IP2, BHS and AAMI protocols.